Expert System Diagnosis of Television Damage with Depth First Search Method Using Vb.Net Programming Language - Dicky Surya Dwi Putra (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2018)
The expert system is part of an artificial intelligence consisting of the knowledge and experience of an expert who is included in the knowledge base. The expert system can help someone who is still lay in solving the problem. Television is a medium of communication that receives broadcasts of moving pictures and sounds. One example of an expert system created is an expert system to diagnose television damage using the Depth First Search method using the VB.NET programming language. With the application of expert systems in diagnosing television damage, expected in the analysis process becomes faster. Expert system analysis on the damage of television can be known directly to assist in knowing what damage experienced by television and what steps to improve television. In this case, the author has consulted with an expert in the field of television damage to build a knowledge base